EKSTRAKSI MINYAK NABATI DARI MIKROALGA SCENEDESSMUS SP. MENGGUNAKAN GELOMBANG ULTRASONIK - Wulan Ari Kristanti; Satwiko S; Noor Fachrizal (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Microalgae is a fuel substitute for oil, have potential to produce vegetable oil far beyond the content of other commodities. The most effective microalgae is CO2 absorbent, so it can be integrated with a system that emits CO2. Ultrasonic extraction method does not involve chemicals, and is used for the extraction of relevant microalgae. This method can also be integrated with non-traditional breeding system, making it more effective and controllable. Expected results of these activities can be a starting point the development of algae as a substitute for fuel oil and can be used to assist the Government in addressing the problem of energy crisis and fuel needs in Indonesia. Keywords: microalgae, extraction, ultrasonic.